Entrepreneurial identity formation through musical identity formation. (8th August 2021) - Hietanen, Lenita; Ruismäki, Heikki
ABSTRACT: Entrepreneurship mostly occurs in business studies after general education. This study considers how the informant, Anna, first identified herself as a young music hobbyist, then as a musician and music teacher, and finally as an entrepreneur in music. The main question driving this narrative study is, 'How might identity formation processes as a musician and a music teacher influence identity formation as an entrepreneur in music?' Anna is an example of an individual who possesses non-business resources that support entrepreneurial identity formation processes earlier in life. The study underlines the importance of ongoing support for an individual's displays of initiative, original ideas and creativity when dealing with opportunities during the entire educational path. Although this case is specific to Finland, the findings could be applied internationally to support people in discovering their entrepreneurial selves and in becoming entrepreneurs as early as possible alongside their hobbies and non-business professions.